Standard methods for the examination of water & wastewater. - American Public Health Association; American Water Works Association; Water Environment Federation; Eaton, Andrew D., ....-; Franson, M. A. H., ....- (Washington, DC : American Public Health Association, 2005)
"The Twenty-First Edition has continued the trend to revise methods as issues are identified and contains further refined quality assurance requirements in a number of Parts [sic] and new data on precision and bias. New methods have been added in Parts 2000, 4000, 5000, 6000, 7000, 8000, and 9000, and numerous methods have been revised. Details of these changes appear on the reverse of the title page for each part."--Pref. p. iv.
Introduction -- Physical and aggregate properties -- Metals -- Inorganic nonmetallic constituents -- Aggregate organic constituents -- Individual organic compounds -- Radioactivity -- Toxicity -- Microbiological examination -- Biological examinations.
Includes bibliographical references and index.
Keywords: Etats-Unis d'Amérique.; Abwasseranalyse; Afvalwateranalyse; Analyse de l'eau.; Déchets industriels; Eau -- Analyse; Eaux usées -- Analyse; Materials testing; Methods Application; Physical Properties; Pollution de l'eau.; Sewage -- Analysis; Sewage -- Analysis; Sewage -- Analysis; Untersuchung (Medizin).; Wasseranalyse; Wassergüte; Water Microbiology; Water Pollution; Water Supply; Water -- Analysis; Water -- Analysis; Water -- Analysis; Wateranalyse